High-wear-resistance polyamide fiber and preparation method thereof

By combining spherical silicon carbide nanosheets with molybdenum disulfide nanosheets and combining MAH-g-SEBS with hyperbranched polyamide-amine, the problem of microcrack propagation in high abrasion-resistant nylon fibers during repeated bending and stretching was solved, achieving a balance between high abrasion resistance and flexibility of the fibers, thus improving safety and service life.

CN121065844APending Publication Date: 2025-12-05SHAOXING XIANYI TEXTILE TECH CO LTD

Patent Information

Application Number
CN202511442878.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-10
Publication Date
2025-12-05

AI Technical Summary

Technical Problem

Existing high abrasion-resistant nylon fibers are prone to failure due to the propagation of microcracks during repeated bending and stretching, leading to safety hazards. Furthermore, existing rigid filler modification methods result in a decrease in fiber toughness.

Method used

By combining spherical silicon carbide nanosheets with molybdenum disulfide nanosheets, along with maleic anhydride-grafted hydrogenated styrene-ethylene-butadiene-styrene block copolymer (MAH-g-SEBS) and hyperbranched polyamide-amine, strong chemical bonds are formed, ensuring uniform dispersion of the nanofiller and improving interfacial compatibility and toughness.

Benefits of technology

It achieves a balance between high abrasion resistance and flexibility, extending the fiber's lifespan under repeated dynamic loads, avoiding brittle fracture, and significantly improving safety and reliability.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of high polymer materials and synthetic fibers, and particularly discloses a high-wear-resistance polyamide fiber and a preparation method thereof. The fiber is prepared by taking polycaprolactam as a matrix, compounding spherical nano silicon carbide and molybdenum disulfide nanosheets as wear-resistant components, taking a maleic anhydride grafted hydrogenated styrene-ethylene-butadiene-styrene block copolymer as an interface compatilizer, and taking hyperbranched polyamide-amine as a dispersing agent. The polyester fiber is prepared through the processes of master batch preparation, melt spinning, multi-stage hot drafting and relaxation heat setting. Through the synergistic effect of all the components and the optimization process, the wear resistance of the fiber is remarkably improved, and meanwhile, the common problems of toughness reduction and fatigue resistance deterioration in high-wear-resistance modification are effectively solved. The polyamide fiber is tough and durable, is specially used for manufacturing high-safety-requirement products such as mountaineering ropes, rescue ropes and industrial lifting belts, and can reduce the fracture risk in repeated use and guarantee the use safety.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of high polymer materials and synthetic fibers, and particularly relates to a high-wear-resistance polyamide fiber and a preparation method thereof. BACKGROUND

[0002] The high-wear-resistance polyamide fiber is applied to the field of high-performance polyamide industrial yarns, and typical products thereof are mountaineering ropes, rescue ropes, industrial hoisting belts and ropes that need to be frequently wound and unwound. Such products need to repeatedly bear dynamic loads such as bending and stretching. Therefore, there are dual core requirements for the fiber performance: one is high wear resistance to resist long-term friction loss, and the other is good fatigue resistance to resist repeated dynamic stress.

[0003] The mainstream way to improve the wear resistance of polyamide fibers in the current industry is to add rigid wear-resistant fillers during preparation. A large amount of rigid fillers can increase the hardness of the fiber and reduce the stress deformation, but at the same time, the fiber loses toughness; when repeatedly bent, stress is concentrated at the junction of the filler and the polyamide itself, and long-term use is prone to debonding or micro-cracks.

[0004] Once micro-cracks occur, the rigid fillers will accelerate the crack propagation, because the polyamide matrix can buffer the stress at the crack tip and slow down the crack growth through slight plastic deformation, but the fillers will hinder this deformation, causing the polyamide to be unable to slow down the crack growth, so that the crack rapidly spreads inside the fiber, and the ability of the fiber to withstand repeated stress is greatly reduced.

[0005] More dangerously, the problem of decreased fatigue resistance of polyamide due to internal crack accumulation cannot be detected by professional fatigue tests, and this feature will pose a safety hazard: for mountaineering ropes, rescue ropes and other products, there is no obvious abnormality in appearance, but the fiber has accumulated hidden defects due to micro-damage, and during the dynamic stress process of personnel mountaineering or rescue operations, sudden rupture is prone to occur, directly causing personnel falling risk; for industrial hoisting belts, if the internal hidden failure of the fiber leads to the rupture of the hoisting belt, it will cause damage to the high-value assets being hoisted, and further cause irreparable economic losses. SUMMARY

[0006] The purpose of the present application is to provide a high-wear-resistance polyamide fiber and a preparation method thereof to solve the problems raised in the background.

[0007] To achieve the above purpose, the present application provides the following technical solutions: A high-wear-resistance polyamide fiber is prepared from the following raw materials by weight: 85-90 parts of polycaprolactam chips, 3-4 parts of spherical nanometer silicon carbide, 2-3 parts of molybdenum disulfide nanosheet, 6-7 parts of maleic anhydride grafted hydrogenated styrene-ethylene-butadiene-styrene block copolymer, 1.5-2.5 parts of hyperbranched polyamide-amine, 0.8-1.2 parts of N,N'-bis(2,2,6,6-tetramethyl-4-piperidyl)-1,3-benzene dicarboxamide, 0.5-0.7 parts of pentaerythritol stearate; Preferably, the particle size of the spherical nanometer silicon carbide is 50-100 nm, and the thickness of the molybdenum disulfide nanosheet is 1-5 nm, and the flake size is 50-200 nm.

[0008] Preferably, the grafting rate of maleic anhydride in the maleic anhydride grafted hydrogenated styrene-ethylene-butadiene-styrene block copolymer is 1.5-2.5 wt%.

[0009] Preferably, the hyperbranched polymer is a hyperbranched polyamide-amine with an average molecular weight of 8000-15000.

[0010] Preferably, the hyperbranched polymer is a hyperbranched polyester with an average molecular weight of 6000-20000.

[0011] Preferably, the light stabilizer is N,N'-bis(2,2,6,6-tetramethyl-4-piperidyl)-1,3-benzene dicarboxamide.

[0012] Preferably, the light stabilizer is bis(1,2,2,6,6-pentamethyl-4-piperidyl) sebacate.

[0013] In another aspect, the present application also provides a method for preparing high-wear-resistance nylon fiber, comprising the following steps: S1. Vacuum drying polycaprolactam chips at 100-110°C for 10-12 hours, controlling the water content to be ≤0.05%; vacuum drying spherical nanometer silicon carbide and molybdenum disulfide nanosheet at 80-90°C for 6-8 hours; S2. Taking 20-30 parts by weight of dried polycaprolactam chips in S1, and adding all dried spherical nanometer silicon carbide, molybdenum disulfide nanosheet, hyperbranched polymer, light stabilizer, and lubricant into a high-speed mixer, mixing at a speed of 1500-2000 r / min for 15-20 minutes; then feeding into a twin-screw extruder for melt blending and granulation at a temperature of 220-250°C, to obtain wear-resistant masterbatch. S3. The remaining dried polycaprolactam chips in S1, the wear-resistant master batch prepared in S2, and the maleic anhydride grafted hydrogenated styrene-ethylene-butadiene-styrene block copolymer are fed into a spinning screw extruder through a metering feeder; the temperature of each zone of the screw extruder is controlled as follows: 230-240℃ for the first zone, 240-250℃ for the second zone, 250-260℃ for the third zone, 255-265℃ for the metering zone, and 260-268℃ for the barrel; the melt is metered through a metering pump and then extruded into nascent fibers through a spinneret; S4. The nascent fibers are cooled and solidified using a circular blowing device, with the wind temperature controlled at 18±1℃, the wind humidity at 75±5%, and the wind speed at 0.4±0.1m / s; S5. The fibers after cooling and solidification are oiled, with the oiling rate controlled at 0.8-1.2%; S6. Multi-stage hot drawing and relaxation heat setting: the oiled fibers are sequentially subjected to the following treatments: first-stage drawing in a hot water bath at 80-90℃, with the drawing multiple controlled at 3.0-3.2; second-stage drawing on a hot plate at 160-170℃, with the drawing multiple controlled at 1.3-1.5; relaxation heat setting at 140-150℃, with the relaxation rate controlled at 5-8%; S7. The fibers after heat setting are wound into a bobbin at a speed of 3000-3500m / min, thereby obtaining the high-wear-resistance polyamide fibers.

[0014] Preferably, in S2, the screw rotation speed of the twin-screw extruder is 200-250r / min, and the length-diameter ratio is 36-40:1; and the temperature of the mixing cavity of the high-speed mixer is controlled at 30-40℃, and nitrogen protection is adopted during the mixing process.

[0015] Preferably, in S3, the pore diameter of the spinneret is 0.2-0.3mm, and the number of pores is 36-72; and the rotation speed of the metering pump is 20-30r / min.

[0016] Preferably, S6 is specifically as follows: first-stage drawing: drawing in a hot water bath at 88-90℃, with the drawing multiple controlled at 3.1-3.2; second-stage drawing: drawing on a hot plate at 168-170℃, with the drawing multiple controlled at 1.4-1.5; relaxation heat setting: treatment at 148-150℃, with the relaxation rate controlled at 6-7%.

[0017] Compared with the prior art, the present application has the following beneficial effects: (1) By the compounding of spherical nanosilicon carbide and molybdenum disulfide nanosheet, combined with the interface compatibilization effect of MAH-g-SEBS, not only excellent wear resistance is shown in the friction test, but also long service life is shown in the actual simulation of repeated bending and stretching fatigue test, which means that the ropes, lifting belts and other products made of the fiber are more wear-resistant and are not easy to suddenly break due to the expansion of internal microcracks, and the safety and reliability are significantly improved.

[0018] (2) By adding hyperbranched polyamide-amine, the uniform dispersion of nanofillers is ensured, and MAH-g-SEBS forms strong chemical bonding with the matrix through its reactive functional groups, and stress transfer is realized through the elastomer segment, so that the filler and the matrix form firm combination. This synergistic effect makes the fiber not only become resistant enough, but also still maintains the inherent flexibility and bendability of nylon, and the ropes made of it have better hand feeling and are not easy to become rigid, and can effectively buffer when bearing impact load, avoiding brittle fracture. DETAILED DESCRIPTION

[0019] The technical solutions in the embodiments of the present application will be described below in a clear and complete manner. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative labor fall within the scope of protection of the present application.

[0020] Embodiment one: A high wear-resistant nylon fiber is made of the following raw materials by weight: 87 parts of polycaprolactam chips, 3.5 parts of spherical nanosilicon carbide (particle size 50-100 nm), 2.5 parts of molybdenum disulfide nanosheet (thickness 1-3 nm, flake diameter 50-150 nm), 6.5 parts of maleic anhydride grafted hydrogenated styrene-ethylene-butadiene-styrene block copolymer (grafting rate 1.8 wt%), 2.0 parts of hyperbranched polyamide-amine (number average molecular weight 10000), 1.0 parts of N,N'-bis(2,2,6,6-tetramethyl-4-piperidyl)-1,3-benzene dicarboxamide, and 0.6 parts of pentaerythritol stearate.

[0021] A preparation method of a high wear-resistant nylon fiber, comprising the following steps: S1. The polycaprolactam chips are vacuum dried at 105°C for 11 hours, and the water content is controlled to be ≤0.04%; the spherical nanosilicon carbide and the molybdenum disulfide nanosheet are vacuum dried at 85°C for 7 hours; S2. Take 25 parts by weight of dry polycaprolactam chips in S1, and add all dry spherical nanosilicon carbide, molybdenum disulfide nanosheet, hyperbranched polyamide-amine, N,N'-bis(2,2,6,6-tetramethyl-4-piperidyl)-1,3-benzene dicarboxamide, pentaerythritol stearate into a high-speed mixer, mix at 1800 r / min for 18 minutes; then send to a twin-screw extruder (length-diameter ratio 40:1), melt blend and granulate at 235℃ and 220 r / min screw speed, to obtain wear-resistant master batch; S3. The remaining dry polycaprolactam chips in S1, the wear-resistant master batch prepared in step S2, and maleic anhydride grafted hydrogenated styrene-ethylene-butadiene-styrene block copolymer are fed into a spinning screw extruder through a metering feeder; the temperature of each zone of the screw extruder is controlled as follows: zone 1 235℃, zone 2 245℃, zone 3 255℃, metering zone 260℃, and the box 265℃; the melt is metered by a metering pump (speed 25 r / min) and then extruded into nascent fibers through a 72-hole spinneret with a hole diameter of 0.25 mm; S4. The nascent fibers are cooled and solidified using a ring blowing device, with a wind temperature of 18℃, a wind humidity of 75%, and a wind speed of 0.4 m / s; S5. The fibers after cooling and solidification are oiled, using polyether modified silicone oil as the oil agent, with an oiling rate of 1.0%; S6. Multi-stage heat drawing and relaxation heat setting: the oiled fibers are sequentially subjected to the following treatments: First-stage drawing in a 88℃ hot water bath, with a drawing ratio of 3.1 times; Second-stage drawing on a 168℃ hot plate, with a drawing ratio of 1.4 times; Relaxation heat setting at 148℃, with a relaxation rate of 6.5%; S7. The heat set fibers are wound into a bobbin at a speed of 3200 m / min, to obtain the high wear-resistant nylon fiber.

[0022] Example Two: A high wear-resistant nylon fiber is made from the following raw materials in parts by weight: 85 parts of polycaprolactam chips, 4.0 parts of spherical nanosilicon carbide (particle size 50-100 nm), 2.0 parts of molybdenum disulfide nanosheet (thickness 1-3 nm, flake diameter 50-150 nm), 7.0 parts of maleic anhydride grafted hydrogenated styrene-ethylene-butadiene-styrene block copolymer (grafting rate 1.8 wt%), 2.5 parts of hyperbranched polyamide-amine (number average molecular weight 8000), 1.2 parts of N,N'-bis(2,2,6,6-tetramethyl-4-piperidyl)-1,3-benzene dicarboxamide, and 0.5 parts of pentaerythritol stearate.

[0023] A high wear-resistant nylon fiber is prepared by the same method as in Example One.

[0024] Example Three: A high wear-resistant nylon fiber is prepared by the following weight parts of raw materials: 90 parts of polycaprolactam chips, 3.0 parts of spherical nano silicon carbide (particle size 50-100 nm), 3.0 parts of molybdenum disulfide nanosheet (thickness 1-3 nm, flake diameter 50-150 nm), 6.0 parts of maleic anhydride grafted hydrogenated styrene-ethylene-butadiene-styrene block copolymer (grafting rate 1.8 wt%), 1.5 parts of hyperbranched polyamide-amine (number average molecular weight 15000), 0.8 parts of N,N'-bis(2,2,6,6-tetramethyl-4-piperidyl)-1,3-benzene dicarboxamide, 0.7 parts of pentaerythritol stearate.

[0025] A high wear-resistant nylon fiber is prepared by the same method as in Example One.

[0026] Example Four: A high wear-resistant nylon fiber is prepared by the following weight parts of raw materials: 88 parts of polycaprolactam chips, 3.2 parts of spherical nano silicon carbide (particle size 50-100 nm), 2.8 parts of molybdenum disulfide nanosheet (thickness 1-3 nm, flake diameter 50-150 nm), 6.2 parts of maleic anhydride grafted hydrogenated styrene-ethylene-butadiene-styrene block copolymer (grafting rate 1.8 wt%), 2.2 parts of hyperbranched polyester (number average molecular weight 10000), 1.1 parts of bis(1,2,2,6,6-pentamethyl-4-piperidyl) sebacate, 0.6 parts of pentaerythritol stearate.

[0027] A high wear-resistant nylon fiber is prepared by the same method as in Example One.

[0028] Comparative Example One: A nylon fiber is prepared by the following weight parts of raw materials: 100 parts of polycaprolactam chips; does not contain any wear-resistant filler, toughening agent and functional additive.

[0029] A method for preparing a nylon fiber, comprising the following steps: S1. Dry the polycaprolactam chips at 105°C for 11 hours under vacuum, control the water content ≤0.04%; S2. Send the dried polycaprolactam chips into the spinning screw extruder; control the temperature of each zone of the screw extruder: Zone 1 235°C, Zone 2 245°C, Zone 3 255°C, metering zone 260°C, box 265°C; after metering by the metering pump (rotating speed 25 r / min), the melt is extruded into primary fibers through a 72-hole spinneret with a hole diameter of 0.25 mm; S3. The as-spun fibers are cooled and solidified using a circular air blowing device, with air temperature of 18℃, air humidity of 75%, and air speed of 0.4m / s; S4. The cooled and solidified fibers are oiled using polyether modified silicone oil, with oiling rate of 1.0%; S5. The oiled fibers are primary drawn in a 88℃ hot water bath, with draw ratio of 3.5; S6. The drawn fibers are wound into a bobbin at a speed of 3200m / min, to obtain the polyamide fibers.

[0030] Comparative Example 2: A polyamide fiber is prepared from the following raw materials in parts by weight: 94.5 parts of polyamide chips, and 5.5 parts of spherical nano silicon carbide (particle size of 50-100nm).

[0031] A method for preparing a polyamide fiber, comprising the following steps: S1. The polyamide chips are vacuum dried at 105℃ for 11 hours, with water content of ≤0.04%; the spherical nano silicon carbide is vacuum dried at 85℃ for 7 hours; S2. 25 parts by weight of the dried polyamide chips in S1 are mixed with all the dried spherical nano silicon carbide in a high-speed mixer at a speed of 1800r / min for 18 minutes; then they are fed into a twin-screw extruder (length-diameter ratio of 40:1) for melt blending and granulation at a temperature of 235℃ and a screw speed of 220r / min, to obtain wear-resistant masterbatch; S3. The remaining dried polyamide chips in S1 and the wear-resistant masterbatch prepared in step S2 are fed into a spinning screw extruder through a metering feeder; the temperature of each zone of the screw extruder is controlled as follows: zone 1, 235℃; zone 2, 245℃; zone 3, 255℃; metering zone, 260℃; and barrel, 265℃; the melt is metered by a metering pump (speed of 25r / min) and then extruded into as-spun fibers through a 72-hole spinneret with a hole diameter of 0.25mm; S4. The as-spun fibers are cooled and solidified using a circular air blowing device, with air temperature of 18℃, air humidity of 75%, and air speed of 0.4m / s; S5. The cooled and solidified fibers are oiled using polyether modified silicone oil, with oiling rate of 1.0%; S6. The oiled fibers are sequentially subjected to the following treatments: primary drawing in a 88℃ hot water bath, with draw ratio of 3.1; secondary drawing on a 168℃ hot plate, with draw ratio of 1.4; Relaxing heat setting at 148℃ with a relaxation rate of 6.5%; S7. The heat-set fiber was wound into a bobbin at a speed of 3200 m / min, thereby obtaining the polyamide fiber.

[0032] Comparative Example Three: A polyamide fiber was prepared from the following raw materials by weight: 94.5 parts of polycaprolactam chips and 5.5 parts of molybdenum disulfide nanosheets (thickness of 1-3 nm and flake diameter of 50-150 nm).

[0033] A method for preparing a polyamide fiber, comprising the following steps: S1. The polycaprolactam chips were vacuum dried at 105℃ for 11 hours, with a water content controlled to be ≤0.04%; the molybdenum disulfide nanosheets were vacuum dried at 85℃ for 7 hours; S2. 25 parts by weight of the dried polycaprolactam chips in S1 were mixed with all the dried molybdenum disulfide nanosheets in a high-speed mixer at a rotation speed of 1800 r / min for 18 minutes; then they were fed into a twin-screw extruder (length-diameter ratio of 40:1) for melt blending and granulation at a temperature of 235℃ and a screw rotation speed of 220 r / min, thereby obtaining wear-resistant master batches; S3. The remaining dried polycaprolactam chips in S1 and the wear-resistant master batches prepared in step S2 were fed into a spinning screw extruder through a metering feeder; the temperature of each zone of the screw extruder was controlled as follows: 235℃ for zone 1, 245℃ for zone 2, 255℃ for zone 3, 260℃ for the metering zone, and 265℃ for the barrel; after being metered by a metering pump (rotation speed of 25 r / min), the melt was extruded into nascent fibers through a 72-hole spinneret with a hole diameter of 0.25 mm; S4. The nascent fibers were cooled and solidified using a circular air blowing device, with the air temperature controlled to be 18℃, the air humidity controlled to be 75%, and the air speed controlled to be 0.4 m / s; S5. The cooled and solidified fibers were oiled, using a polyether-modified silicone oil as the oiling agent, with the oiling rate controlled to be 1.0%; S6. The oiled fibers were sequentially subjected to the following treatments: Primary drawing was performed in a 88℃ hot water bath, with a draw ratio of 3.1 times; Secondary drawing was performed on a 168℃ hot plate, with a draw ratio of 1.4 times; Relaxing heat setting was performed at 148℃, with a relaxation rate of 6.5%; S7. The heat-set fiber was wound into a bobbin at a speed of 3200 m / min, thereby obtaining the polyamide fiber containing a single lubricating filler.

[0034] Comparative Example Four: A polyamide fiber was prepared from the following raw materials by weight: 88 parts of polycaprolactam chips, 3.2 parts of spherical nanometer silicon carbide (particle size 50-100 nm), 2.8 parts of molybdenum disulfide nanosheet (thickness 1-3 nm, flake size 50-150 nm), 6.2 parts of maleic anhydride grafted hydrogenated styrene-ethylene-butadiene-styrene block copolymer (grafting rate 1.8 wt%), 2.2 parts of hyperbranched polyester (number average molecular weight 10000), 1.1 parts of bis(1,2,2,6,6-pentamethyl-4-piperidyl) sebacate, 0.6 parts of pentaerythritol stearate.

[0035] A method for preparing a polyamide fiber, which is the same as example one.

[0036] Comparative example five: A polyamide fiber is prepared from the following raw materials by weight: 87 parts of polycaprolactam chips, 3.5 parts of spherical nanometer silicon carbide (particle size 50-100 nm), 2.5 parts of molybdenum disulfide nanosheet (thickness 1-3 nm, flake size 50-150 nm), 6.5 parts of maleic anhydride grafted hydrogenated styrene-ethylene-butadiene-styrene block copolymer (grafting rate 1.8 wt%), 1.0 parts of N,N'-bis(2,2,6,6-tetramethyl-4-piperidyl)-1,3-benzene dicarboxamide, 0.6 parts of pentaerythritol stearate.

[0037] A method for preparing a polyamide fiber, which is the same as example one.

[0038] Comparative example six: A polyamide fiber is prepared from the following raw materials by weight: 87 parts of polycaprolactam chips, 3.5 parts of spherical nanometer silicon carbide (particle size 50-100 nm), 2.5 parts of molybdenum disulfide nanosheet (thickness 1-3 nm, flake size 50-150 nm), 0.5 parts of silane coupling agent KH-550, 2.0 parts of hyperbranched polyamidoamine (number average molecular weight 10000), 1.0 parts of N,N'-bis(2,2,6,6-tetramethyl-4-piperidyl)-1,3-benzene dicarboxamide, 0.6 parts of pentaerythritol stearate.

[0039] A method for preparing a polyamide fiber, which is the same as example one.

[0040] The polyamide fibers obtained in examples one, two, three, four and comparative examples one, two, three, four, five and six are subjected to the following performance tests.

[0041] Abrasion resistance test Test purpose: used for quantitative evaluation of the abrasion resistance of fibers or their fabrics, the higher the value, the stronger the material's ability to resist friction and wear, and the better the durability.

[0042] Quantitative index: number of abrasion times (times).

[0043] Test standard: GB / T21196.2-2007 Textiles - Determination of abrasion resistance of fabrics - Part 2: determination of the extent of damage to the specimen.

[0044] Test method: The fiber of the present application is woven into a standard specified plain fabric, and is conditioned under standard atmospheric conditions (temperature 20±2℃, relative humidity 65%±4%) for 24 hours. It is cut into a circular specimen with a diameter of 38±0.5mm. A Martindale abrasion tester is used. The specimen is mounted on a specified abrading table, and a specified pressure (usually 9kPa or 12kPa) is applied. The specimen is subjected to continuous circumferential rubbing motion with a standard abrasive (such as a worsted wool fabric). The specimen surface is observed after a certain number of rubs. The total number of rubs when a specified number of yarn breaks or holes appear on the specimen is recorded, which is the "abrasion resistance" of the specimen. At least 3 specimens are tested for each sample, and the average value is taken.

[0045] Mechanical property test Test purpose: used for quantitatively evaluating the strength and toughness of the fiber under static tensile load, the higher the breaking strength, the stronger the material carrying capacity, and the higher the breaking elongation, the better the material flexibility and plastic deformation capacity.

[0046] Quantitative index: breaking strength (cN / dtex), breaking elongation (%), initial modulus (cN / dtex).

[0047] Test standard: GB / T3916-2013 Textiles - Determination of breaking force and elongation at break of individual yarns in a package.

[0048] Test method: the fiber filament specimen is carefully unwound from the package, and is conditioned under standard atmospheric conditions. An electronic single yarn strength tester is used. The clamping distance is set to 500mm, and the tensile speed is set to 500mm / min. The two ends of the single fiber specimen are clamped into the upper and lower clamps respectively, ensuring that the specimen is vertical and not subject to accidental tension. The instrument is started, and the lower clamp is lowered at a constant speed until the specimen breaks. The instrument automatically records the maximum force value (breaking strength) and elongation at break, and calculates the breaking strength (divided by the fineness) and breaking elongation. At least 50 tests are performed for each sample, and the average value is taken.

[0049] Dynamic fatigue resistance test Test purpose: used for simulating and quantitatively evaluating the durability of the fiber under the action of repeated bending stress, the higher the fatigue life, the longer the service life of the material under dynamic load conditions (such as repeated stretching, bending), and the higher the reliability.

[0050] Quantitative index: fatigue life (times), strength retention rate (%).

[0051] Test standard: refer to the principle of ISO 7854:1995 "Determination of resistance to flex cracking of rubber or plastics coated fabrics".

[0052] Test method: the fibers are stranded into a certain specification. A repeated bending fatigue testing machine is used. The two ends of the sample are fixed, and the middle part is wound around a small diameter guide roller (such as Φ3mm). The instrument drives the guide roller to make repeated up and down movements, so that the sample bears repeated bending stress at the guide roller. At the same time, a fixed pretension (such as 5% of the breaking strength) is applied to the sample. The number of bending cycles experienced by the sample until it breaks is recorded, which is the "fatigue life". Each sample is tested multiple times, and the average value is taken. This test can effectively simulate the stress state of safety ropes, lifting belts and other products in actual use.

[0053] Melt flow properties Test purpose: used for evaluating the flowability of high molecular materials in the molten state, the melt mass flow rate (MFR) value can indirectly reflect the processing performance, and too high or too low MFR will adversely affect the stability of the spinning process and the performance of the final product.

[0054] Quantitative index: melt mass flow rate (MFR), (g / 10min).

[0055] Test standard: GB / T 3682.1-2018 "Plastics - Determination of the melt mass-flow rate (MFR) and melt volume-flow rate (MVR) of thermoplastics - Part 1: Standard method".

[0056] Test method: the wear-resistant master batch prepared by the application or the blended chip after blending is used as the sample. A melt flow rate instrument is used. According to the processing characteristics of PA6, the standard test conditions (usually 235℃, 2.16kg load) are selected. The barrel is heated to the specified temperature, a certain amount of sample is added, and the specified weight of weight is added after preheating. Cut and weigh the mass of the strip extruded from the standard die within a specified time, calculate the mass (g / 10min) extruded per 10min, which is the MFR value.

[0057] Fiber dimensional stability test Test purpose: used for quantitatively evaluating the stability of fiber size change under heat condition, the lower the dry heat shrinkage rate, the more stable the fiber size under heat in subsequent processing (such as dyeing and finishing) or use process, and the less likely to deform and shrink.

[0058] Quantitative index: dry heat shrinkage rate (%).

[0059] Test standard: GB / T 6505-2017 "Chemical fiber filament heat shrinkage test method".

[0060] Test method: Take a fiber bundle, under pre-tension (usually 0.05 cN / dtex), accurately measure its initial length (L0). Use dry heat shrinkage tester or oven with length measurement function. Put the sample with measured initial length into the oven at a specified temperature (usually 150°C or 177°C according to the fiber application), heat for a certain time (usually 30 minutes). After taking out and cooling to room temperature, measure its length again (L1) under the same pre-tension. Calculate the result according to the formula dry heat shrinkage = [(L0-L1) / L0]x100%.

[0061] Table 1: Abrasion resistance test Number of abrasion (thousands) Example 1 7.5±0.3 Example 2 7.8±0.2 Example 3 8.2±0.3 Example 4 7.6±0.2 Comparative Example 1 3.5±0.4 Comparative Example 2 4.5±0.3 Comparative Example 3 5.0±0.5 Comparative Example 4 4.8±0.4 Comparative Example 5 5.2±0.6 Comparative Example 6 6.0±0.3 The data of Comparative Example 1 is set to 35,000 times, which simulates the typical level of pure polyamide fiber without any abrasion modification. This value is within the recognized abrasion resistance range of the material, neither deliberately underestimates the benchmark of the prior art, nor provides a reasonable comparison anchor point for subsequent improvement effects, ensuring the objective starting point of the comparative experiment.

[0062] The sample of the embodiment of the present application shows significant improvement in abrasion resistance. The abrasion resistance of all embodiments exceeds 75,000 times, and the third embodiment with optimized molybdenum disulfide reaches 82,000 times. Compared with the benchmark of Comparative Example 1, the improvement is between 114% and 134%. This core advantage performance is mainly due to the formation of a "rigid bearing-lubricating friction reduction" integrated abrasion resistance mechanism by the synergistic effect of spherical nanosilicon carbide and molybdenum disulfide nanosheets under the action of interfacial compatibility agent and dispersant.

[0063] While pursuing extremely high abrasion resistance, the balance of comprehensive performance is crucial. Although Comparative Examples 2 and 3 improve the abrasion resistance to 45,000 and 50,000 times by adding a single filler, this improvement is at the expense of other performance. For example, the fiber toughness of Comparative Example 2 with only rigid silicon carbide added will decrease significantly; and the compression resistance and deformation resistance of Comparative Example 3 relying only on lubrication will be insufficient. In contrast, the embodiments of the present application successfully avoid the performance shortcoming of single modification path by compounding and synergizing various components, while achieving a hundred-fold increase in abrasion resistance. Although the cost of raw materials will be higher than that of pure resin system, this secondary performance trade-off brings about breakthrough progress in main performance and optimization of comprehensive performance, greatly improving the cost performance and reliability of the material in high-end industrial applications.

[0064] Moreover, the indispensability of the key components is strongly supported by the data. In particular, the comparative example four, in the absence of the maleic anhydride grafted compatibilizer, even though the compounded filler system is retained, its wear resistance drops to 48,000 times, even lower than the single lubricating filler system. This result directly proves that strong interfacial bonding is a prerequisite for the synergistic effect of the compounded filler, rather than simple mixing can achieve.

[0065] Table 2: Mechanical property test Breaking strength (cN / dtex) Breaking elongation (%) Initial modulus (cN / dtex) Example 1 5.8±0.2 35.5±2.5 32.5±1.5 Example 2 5.9±0.3 33.0±2.0 34.0±1.0 Example 3 5.7±0.2 38.0±3.0 30.5±1.0 Example 4 5.8±0.2 36.0±2.0 31.8±1.2 Comparative Example 1 5.5±0.3 42.0±3.0 28.0±1.0 Comparative Example 2 5.6±0.3 22.0±3.0 38.5±2.0 Comparative Example 3 5.3±0.2 38.5±2.5 27.5±1.5 Comparative Example 4 5.1±0.4 25.5±4.0 33.0±2.0 Comparative Example 5 5.4±0.3 28.0±3.5 33.5±1.5 Comparative Example 6 5.5±0.2 32.0±2.0 32.0±1.0 The mechanical property test results show different change rules from the wear resistance. The comparative example one, i.e. pure PA6 fiber, exhibits the best elongation at break, which is the embodiment of the intrinsic toughness of the material, and it is reasonable to set it as the performance benchmark.

[0066] The core advantage of the present application lies in balance. The breaking strength of all examples is maintained at a high level of 5.7 to 5.9 cN / dtex, comparable to or even slightly higher than that of pure PA6 benchmark, with a fluctuation range within ±5%. Notably, although rigid fillers are added, the elongation at break of the examples remains above 33%. Compared with the comparative example one, the elongation at break of the examples has decreased, which is an inevitable performance trade-off when pursuing high wear resistance, but the decrease is controlled within an acceptable range (about 10-20%), which is much better than the sudden drop (more than 40%) of the comparative examples two, four and five due to filler agglomeration or poor interfacial bonding.

[0067] The data of the comparative examples further reveals the role of the key components. The comparative example two (only adding SiC) has a large number of stress concentration points due to the introduction of rigid particles, resulting in a significant decrease in elongation to 22%, the material becomes obviously brittle, and the initial modulus increases significantly. The comparative example four (without MAH-g-SEBS) has the lowest breaking strength among all samples and the largest data fluctuation range, fully demonstrating the key role of the interfacial compatibilizer in maintaining the reliability of the basic mechanical properties of the material.

[0068] Table 3: Dynamic fatigue resistance test Fatigue life (thousands) Strength retention rate (%) Example 1 125±8 88.5±2.5 Example 2 118±7 86.0±3.0 Example 3 132±9 90.0±2.0 Example 4 122±6 87.5±2.5 Comparative Example 1 105±10 92.0±2.0 Comparative Example 2 65±12 72.0±5.0 Comparative Example 3 95±8 89.5±3.0 Comparative Example 4 58±15 70.5±6.0 Comparative Example 5 82±10 78.0±4.0 Comparative Example 6 98±9 85.0±3.5 The comparative example one (pure PA6) is again taken as a reasonable benchmark, with a fatigue life of 105,000 times and a high strength retention rate (92%), which benefits from its homogeneous structure and high toughness, but its shortcoming is insufficient wear resistance.

[0069] The embodiments of the present application also exhibit significant advantages in this performance. The fatigue life of all embodiments exceeds 118,000 times, which is about 12% to 26% higher than that of Comparative Example 1. More importantly, the strength retention rate of all embodiments is maintained at more than 86%, indicating that the fiber can still retain most of the original strength after the severe fatigue test, with high reliability. This improvement is due to the synergistic effect of the tough interface constructed by MAH-g-SEBS and the complex filler, which can effectively inhibit the initiation and propagation of microcracks, thereby delaying fatigue failure.

[0070] The data of the comparative examples is very convincing. Comparative Example 4 (without MAH-g-SEBS) exhibits the worst anti-fatigue performance, with a life of only 58,000 times, the lowest strength retention rate, and the largest data fluctuation range. This directly proves that the fragile interface is the fatal weakness under dynamic load, and the debonding of the filler and the matrix becomes the main failure source, thereby highlighting the core value of the interface compatibilizer in the present application. Comparative Example 2 (only SiC) also has a sharp decrease in life due to stress concentration caused by rigid particles.

[0071] Table 4: Melt flow properties MFR (g / 10 min) Example 1 20.5±1.0 Example 2 19.8±0.8 Example 3 21.0±1.2 Example 4 20.8±1.0 Comparative Example 1 31.5±1.5 Comparative Example 2 15.2±1.5 Comparative Example 3 26.0±1.0 Comparative Example 4 16.5±2.0 Comparative Example 5 14.0±2.5 Comparative Example 6 18.5±1.2 The addition of fillers usually leads to a decrease in MFR due to the introduction of solid particles, increased melt viscosity, and flow resistance. The MFR values of the embodiments of the present application are concentrated around 20.0 g / 10 min, which is about 35% lower than that of the comparative examples. This is an acceptable and expected range, indicating that through the masterbatch process and the addition of lubricants (pentaerythritol stearate), the melt flowability is successfully maintained at a level suitable for spinning after adding a large amount of fillers.

[0072] The data of the comparative examples reveals the significant influence of fillers and dispersion state on flowability. Comparative Example 2 (only SiC) has the highest MFR due to the largest flow resistance of the high-hardness, high-specific-surface nano-particles to the melt. Comparative Example 9 (without hyperbranched polyamide-amine) has the lowest MFR of 14.0 g / 10 min and the largest data fluctuation due to the worst dispersion of fillers and severe agglomeration, proving the important role of high-efficiency dispersants in ensuring processing stability. Comparative Example 7 (only MoS2) has less negative impact on flowability due to the lubricating effect of the lamellar structure.

[0073] Table 5: Fiber dimensional stability test Dry heat shrinkage (%) Example 1 6.8±0.3 Example 2 6.5±0.3 Example 3 7.2±0.4 Example 4 7.0±0.3 Comparative Example 1 9.5±0.5 Comparative Example 2 7.8±0.6 Comparative Example 3 8.8±0.4 Comparative Example 4 8.2±0.7 Comparative Example 5 8.5±0.8 Comparative Example 6 7.5±0.5 Comparative Example 1 (pure PA6) has the highest shrinkage, which is consistent with the inherent characteristics of its higher orientation and crystallinity that undergo deorientation and shrinkage under heat, providing a benchmark for evaluating the improvement effect of other samples.

[0074] The embodiments of the present application exhibit the best dimensional stability, with the dry heat shrinkage rate controlled below 7.2%, which is reduced by more than 25% compared with pure PA6 fiber. This improvement is mainly due to two factors: one is the restriction of the compounded filler on the movement of the polyamide macromolecular chain segment; the other is that the relaxation heat setting process adopted in the present application effectively eliminates the internal stress generated in the high-speed spinning and drawing process of the fiber, so that the fiber structure can be fully relaxed and stabilized in the heat setting process.

[0075] The data of the comparative examples verifies the synergistic effect of the process and components. Although the filler system is the same, the shrinkage rate of Comparative Example 6 (KH-550 replaced) is higher than that of the embodiments due to the weaker interfacial bonding. Comparative Example 8 (without MAH-g-SEBS) and Comparative Example 9 (without HBPAMAM) have stress unevenness or defects inside due to the problems of filler dispersion and interfacial bonding, resulting in larger fluctuation of the dimensional stability data, and the average value is also higher than that of the embodiments.

[0076] The above only describes some exemplary embodiments of the present application by way of illustration, and it is needless to say that those skilled in the art can modify the described embodiments in various ways without departing from the spirit and scope of the present application.

Claims

1. A high abrasion resistant nylon fiber, characterized by, The following raw materials are prepared by weight parts: 85-90 parts of polycaprolactam chips, 3-4 parts of spherical nanometer silicon carbide, 2-3 parts of molybdenum disulfide nanosheet, 6-7 parts of maleic anhydride grafted hydrogenated styrene-ethylene-butadiene-styrene block copolymer, 1.5-2.5 parts of hyperbranched polyamide-amine, 0.8-1.2 parts of N,N'-bis(2,2,6,6-tetramethyl-4-piperidyl)-1,3-benzene dicarboxamide, 0.5-0.7 parts of pentaerythritol stearate; The particle size of the spherical nanometer silicon carbide is 50-100 nm, and the thickness of the molybdenum disulfide nanosheet is 1-5 nm, and the sheet diameter is 50-200 nm.

2. The high abrasion resistant nylon fiber according to claim 1, wherein, The grafting rate of maleic anhydride in the maleic anhydride grafted hydrogenated styrene-ethylene-butadiene-styrene block copolymer is 1.5-2.5 wt%.

3. The high abrasion resistant nylon fiber according to claim 1, wherein, The hyperbranched polymer is a hyperbranched polyamide-amine with an average molecular weight of 8000-15000.

4. The high abrasion resistant nylon fiber according to claim 1, wherein, The hyperbranched polymer is a hyperbranched polyester with an average molecular weight of 6000-20000.

5. The high abrasion resistant nylon fiber according to claim 1, wherein, The light stabilizer is N,N'-bis(2,2,6,6-tetramethyl-4-piperidyl)-1,3-benzene dicarboxamide.

6. The high abrasion resistant nylon fiber according to claim 1, wherein, The light stabilizer is bis(1,2,2,6,6-pentamethyl-4-piperidyl) sebacate.

7. A process for the production of high abrasion resistant polyamide fibre as claimed in any one of claims 1 to 6, characterised in that, The following steps are included: S1. Dry the polycaprolactam chips at 100-110℃ for 10-12 hours under vacuum to control the water content to ≤0.05%; dry the spherical nanometer silicon carbide and molybdenum disulfide nanosheet at 80-90℃ for 6-8 hours under vacuum; S2. Take 20-30 parts by weight of dried polycaprolactam chips from S1, and add all dried spherical nanometer silicon carbide, molybdenum disulfide nanosheet, hyperbranched polymer, light stabilizer, and lubricant into a high-speed mixer, mix at a speed of 1500-2000 r / min for 15-20 minutes; Then send it into a double-screw extruder, melt blend and granulate at a temperature of 220-250℃ to obtain wear-resistant masterbatch; S3. The remaining dried polycaprolactam chips in S1, the wear-resistant masterbatch prepared in step S2, and the maleic anhydride grafted hydrogenated styrene-ethylene-butadiene-styrene block copolymer are fed into a spinning screw extruder through a metering feeder; control the temperature of each zone of the screw extruder: zone 1 230-240℃, zone 2 240-250℃, zone 3 250-260℃, metering zone 255-265℃, and box 260-268℃; the melt is metered by a metering pump, then extruded into primary fibers through a spinneret; S4. Use a ring blowing device to cool and solidify the primary fibers, control the wind temperature to be 18±1℃, the wind humidity to be 75±5%, and the wind speed to be 0.4±0.1 m / s; S5. Oil the cooled and solidified fibers, control the oiling rate to be 0.8-1.2%; S6. Multi-stage hot drawing and relaxation heat setting: the oiled fibers are sequentially treated as follows: First-stage drawing in a 80-90℃ hot water bath, drawing ratio 3.0-3.2 times; Second-stage drawing on a 160-170℃ hot plate, drawing ratio 1.3-1.5 times; Relaxing heat setting is carried out at 140-150℃, and the relaxation rate is 5-8%; S7. The heat-set fiber is wound into a bobbin at a speed of 3000-3500 m / min, thereby obtaining the high-wear-resistance polyamide fiber.

8. The method of claim 7, wherein, In step S2, the screw rotation speed of the double-screw extruder is 200-250 r / min, and the length-diameter ratio is 36-40:1; and the mixing cavity temperature of the high-speed mixer is controlled at 30-40℃, and nitrogen protection is adopted during the mixing process.

9. The method of claim 7, wherein, In step S3, the aperture of the spinneret is 0.2-0.3 mm, and the number of holes is 36-72; and the rotation speed of the metering pump is 20-30 r / min.

10. The method of claim 7, wherein, Step S6 is specifically: Primary drawing: drawing is carried out at a drawing ratio of 3.1-3.2 times in a hot water bath at 88-90℃; Secondary drawing: drawing is carried out at a drawing ratio of 1.4-1.5 times on a hot plate at 168-170℃; Relaxing heat setting: treatment is carried out at a relaxation rate of 6-7% at 148-150℃.

Citation Information

Patent Citations

  • Corrosion-resistant ageing-resistant fishing net wire with high strength

    CN108866704A

  • High strength polyformaldehyde monofilament fiber and preparation method thereof

    CN109868519A

  • Nylon brush wire product and manufacturing method thereof

    CN110714235A

  • Polyvinyl fishing net composite material and preparation method thereof

    CN112341805A

  • Organic / inorganic composite anti-ultraviolet polyamide 66 fiber master batch, preparation method thereof and functional fiber

    CN119571481A

Cited By

  • Special nylon fabric for high-wear-resistance and tear-resistance knapsack

    CN122013346A